2014
DOI: 10.7314/apjcp.2014.15.16.6511
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Thrombocytosis in Clinicopathologic Characteristics and Prognosis of Gastric Cancer

Abstract: Purpose: We aimed to study the relationship between thrombocytosis and clinical features of gastric cancerfocussing on platelet counts and gastric cancer progression through different TNM stages. Methods: According to the normal range of platelet count in our institution, 1,596 patients were divided to two groups: a thrombocytosis group (120 patients, >400×1000/μL) and a control group (1,476 patients, ≤400×1000/μL). Results: The incidence of thrombocytosis was 7.5%. Higher platelet counts were observed in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 34 publications
0
21
0
1
Order By: Relevance
“…Four articles reported the link between preoperative platelet count and lymph node metastasis [6,11,26,27]. The incidence of lymph node metastasis was 1.62-fold higher in patients with elevated platelet count than in patients with normal platelet count (OR=1.62, 95% CI: 1.08-2.42, P=0.019) (Fig.…”
Section: The Prognostic Value Of Elevated Platelet Countmentioning
confidence: 99%
See 1 more Smart Citation
“…Four articles reported the link between preoperative platelet count and lymph node metastasis [6,11,26,27]. The incidence of lymph node metastasis was 1.62-fold higher in patients with elevated platelet count than in patients with normal platelet count (OR=1.62, 95% CI: 1.08-2.42, P=0.019) (Fig.…”
Section: The Prognostic Value Of Elevated Platelet Countmentioning
confidence: 99%
“…3A). Data for investigating the correlation between elevated platelet count and depth of tumor invasion (serosal invasion: positive (T3+T4) and negative (T1+T2) ) were available from 4 studies [6,11,26,27], the pooled analysis demonstrated that the incidence of serosal invasion (T3+T4) in patients with elevated platelet count was 2.09-fold higher than in patients with normal platelet count (OR=2.09, 95%CI 1.57-2.77, P <0.001) (Fig. 3B).…”
Section: The Prognostic Value Of Elevated Platelet Countmentioning
confidence: 99%
“…On multivariate analysis for OS, higher platelet count >400000/cu mm conferred a poor prognosis. Poorer outcome with higher platelet count (>400000/cu mm) was also described by Li, et al [13]. In a multivariate prognostic factor analysis by Chau, et al in locally advanced/metastatic gastric cancer patients, ECOG performance status ≥2, high alkaline phosphatase level (>100 U/L) and site of metastasis (peritoneum, liver) had poor outcome [22].…”
Section: Kayal S Austin Publishing Groupmentioning
confidence: 65%
“…Submit your Manuscript | www.austinpublishinggroup.com presented with increased platelet count and this was associated with poor prognosis [13].…”
Section: Kayal S Austin Publishing Groupmentioning
confidence: 99%
“…A total of 20 studies (7,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) that met the inclusion criteria were retrieved for analysis in the present study. The selection process of the included studies is presented in Fig.…”
Section: Identification Of Eligible Studiesmentioning
confidence: 99%